AB1351-HPR A HAND EXERCISES MHEALTH APP FOR PATIENTS WITH RHEUMATOID ARTHRITIS: DEVELOPMENT, DESIGN AND USABILITY STUDY IN TURKEY. (2nd June 2020) - Tonga, E.; Srikesavan, C.; Williamson, E.; Lamb, S.
Abstract : Background: The Strengthening and Stretching for Rheumatoid Arthritis of the Hand (SARAH) programme has been shown to provide long term improvement in hand function for patients with rheumatoid arthritis (RA) affecting their hands. In Turkey, limited number of physiotherapists work in rheumatology departments so there is an opportunity to use the digital technologies for exercise prescription and follow up to improve access to treatment.Growing research evidence supports the effectiveness of mHealth interventions for improving exercise adherence and motivation.To our knowledge, there is no hand exercises mHealth program for patients with rheumatoid arthritis designed by experts with the user-centered method. Objectives: The aim of our study is to develop and design a smartphone application for structured hand exercise program for patients with RA in Turkey and to test its usability. Methods: We used a qualitative user-centered design approach with 2 phases.PHASE 1:we conducted focus group meetings to discuss the content, feature and design of app to produce a prototype version of smartphone software for RA hand training program.The Focus Group consisted of two physiotherapists and three hand therapists working in the field in different rheumatology or hand rehabilitation clinics, two software-computer engineers, and three patients with RA who had previously participated in hand therapy. The focus group met 4 times during phase 1. PHASE 2:we investigated the usability of prototype version of the rheumatoid hand exercise smartphone app software. All focus group members (n=10) and 6 patients used the app for one week.All users filled the usability questionnaire and provided written feedback on the app. Revisions were made and the revised version was tested. We put the revised app in digital markets in Turkish and English. Results: The major themes identified from the Focus Group discussions during phase 1 were (a)Login techniques (b)self-monitoring (c)exercises types/frequency/diary, (d) patient education, (e)behavioral change and encouragement (f)exercise adherence. Patients and therapist all agreed the login needed to be easy. Patients wanted to be able to monitor their pain levels and hand function in the app. Patients thought the SARAH exercise were suitable for the app. A patient said: 'SARAH exercises is beneficial for my hand and tendon gliding exercise, I will be happy to see these exercises in app' . Patients wanted exercise reminders using push up notifications to encourage exercise were proposed and included.A patient commented 'in the morning and after work, motivational push up messages could be beneficial for exercise habit ."During the phase 2, we identified a need for education on how to use digital app, ways to provide patient follow up to monitor adherence, the need to allow patients to select the amount of notifications. This feedback was incorporated into the final version. Conclusion: mHealth applications represent an easily accessible bridge between patients and health professionals for home-based programs. Using a user-centered approach ensured that we developed an application that met the needs of therapists and patients. Physiotherapists are using the app in rheumatology clinics in Turkey and long-term usability and feasibility studies are ongoing. References: [1]Argent R, Patient Involvement With Home-Based Exercise Programs: Can Connected Health Interventions Influence Adherence? JMIR Mhealth Uhealth 2018. [2]Lamb SE, Strengthening and Stretching for Rheumatoid Arthritis of the Hand Trial (SARAH).Lancet. 2015, 385(9966). [3]Azevedo R, Smartphone application for rheumatoid arthritis self-management: cross-sectional study revealed the usefulness, willingness to use and patients' needs.Rheumatol Int.2015, 35(10). Disclosure of Interests: None declared